2020
DOI: 10.3390/su12114680
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Method Study of Design Practices and Designers’ Roles in Sustainable-Minded Clothing Companies

Abstract: The way in which the current fashion industry operates needs to fundamentally change. In this endeavour, designers are considered central figures throughout the sustainable fashion literature. However, too little is known about clothing designers’ practical contributions to sustainability. Therefore, this study investigates how sustainability is integrated into design practices in sustainable-minded clothing companies and determines the role of clothing designers in this respect. A mixed-method study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…To support the transition of fashion brands to sustainability, thus reducing the negative impacts on the environment and society of present practices, Karell and Niinimäki (2020) [22] highlight the need for empirical study to assess the actual implementation of sustainability practices, to bridge the gap between theoretical knowledge and practice. Specifically in the realm of Supply Chain Management, research is needed, as suggested by Brun et al (2020) [21], to further investigate how to overcome the hurdles to sustainably-oriented collaboration, as well as how new emerging technology, e.g., block chain, can support increasing transparency and enable new sustainable business models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To support the transition of fashion brands to sustainability, thus reducing the negative impacts on the environment and society of present practices, Karell and Niinimäki (2020) [22] highlight the need for empirical study to assess the actual implementation of sustainability practices, to bridge the gap between theoretical knowledge and practice. Specifically in the realm of Supply Chain Management, research is needed, as suggested by Brun et al (2020) [21], to further investigate how to overcome the hurdles to sustainably-oriented collaboration, as well as how new emerging technology, e.g., block chain, can support increasing transparency and enable new sustainable business models.…”
Section: Discussionmentioning
confidence: 99%
“…From a managerial perspective, it means practitioners aiming to increase fashion brand sustainability should build long-term and constructive collaborations between supply chain actors. Karell and Niinimäki (2020) [22] look inside the company to open up the design process and discuss how sustainability can be integrated into design and the role of clothing designers in reaching brands' sustainable objectives. Using expert interviews and a survey, they investigate sustainable design practices and the role of clothes designers in sustainably-minded companies.…”
Section: Overview Of the Papersmentioning
confidence: 99%
“…But there still seems to be very little positive impact in regards to circularity coming from the design departments in medium and large organizations. In this article as well as in a lot of the design-research, fashion designers are often described as 'Agents of Change' in the industry, but the actual effect of their efforts is still very limited and so is the knowledge about their actual contributions to sustainability in the companies (Karell and Niinim€ aki 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Even if there are multiple design methods proposed to plan how materials can stay in circulation for a longer period of time, (i.e:. design for longevity, design for reuse or design for services) (Niinim€ aki 2017), CE calls for radical innovation as there are multiple barriers to consider: technological, organizational, financial, structural, operational and attitudinal (Karell and Niinim€ aki 2020;Ritz en and Sandstr€ om 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation